1982
DOI: 10.1159/000123348
|View full text |Cite
|
Sign up to set email alerts
|

Hamster Prolactin: Physiological Changes in Blood and Pituitary Concentrations as Measured by a Homologous Radioimmunoassay

Abstract: A specific and sensitive homologous radioimmunoassay (RIA) for determination of hamster prolactin is described and compared to heterologous hamster prolactin RIA and to the homologous and heterologous RIAs for rat prolactin. With this method, we have determined that, in the golden hamster, diurnal plasma prolactin fluctuations have a mean interpeak interval of 1.5 h, that serum prolactin concentrations are influenced by day length, by ether vapors, by animal’s gender, and by refeeding following a fast but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 23 publications
5
28
0
Order By: Relevance
“…Our immunohistochemical results revealed similar changes on the pituitary lactotropes in male golden hamsters submitted to short periods, although different from those periods used by Wang et al Other studies have previously shown that both PRL synthesis and release are severely inhibited in hamsters exposed to SP [22, 23]. On the other hand, Massa and Blask [24]found that light deprivation due to blindness or to exposure to SP for 42–56 days depresses the activity of the lactotrope cells in Syrian hamsters, with significant diminution of the pituitary levels of PRL mRNA.…”
Section: Discussionsupporting
confidence: 70%
“…Our immunohistochemical results revealed similar changes on the pituitary lactotropes in male golden hamsters submitted to short periods, although different from those periods used by Wang et al Other studies have previously shown that both PRL synthesis and release are severely inhibited in hamsters exposed to SP [22, 23]. On the other hand, Massa and Blask [24]found that light deprivation due to blindness or to exposure to SP for 42–56 days depresses the activity of the lactotrope cells in Syrian hamsters, with significant diminution of the pituitary levels of PRL mRNA.…”
Section: Discussionsupporting
confidence: 70%
“…The acrophase of serum PRL in the indooranimals(= 20.00 h) is close to the peak in serum PRL observed by Goldman et al [12] in both stressed and non-stressed male hamsters exposed to 14:10 LD (lights on 05.00). Another study [35] examined PRL concentrations throughout a 24-hour fasting and 12-hour refeeding period in male hamsters. However, comparison of our data with their [35] results is impossible since the time of day at which the starvation began was not given, although it is interesting that refeeding was associated with a sharp rise in PRL.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [35] examined PRL concentrations throughout a 24-hour fasting and 12-hour refeeding period in male hamsters. However, comparison of our data with their [35] results is impossible since the time of day at which the starvation began was not given, although it is interesting that refeeding was associated with a sharp rise in PRL.…”
Section: Discussionmentioning
confidence: 99%
“…Although certain neuroendocrine responses to stress may be adaptive mechanisms, the analysis of GH secretion in organisms under stressful conditions has an important aspect in understanding the physiology of stress. Numerous observations have shown that stress alters the pattern of GH secretion in a different manner in various species; in hamsters (Borer et al, 1982), monkeys (Brown et al, 1971;Meyer and Knobil, 1987) and men (Schalch, 1967;Schalch and Reichlin, 1968) stress increases GH secretion, while in rats (Day et al, 1983;Armario et al, 1986;Aquila et al, 1991;Benyassi et al, 1992;Franci etal., 1992) GH secretion is inhibited. Little is known about GH secretion under stressful conditions in farm animals.…”
Section: Introductionmentioning
confidence: 99%